The role of economic efficiency in achieving water sustainability in the West Bank and Gaza Strip in Palestine - Rammal, Fuad Yousef; Alkhazzan, Bouchta (Journal of Economic, Administrative and Legal Sciences, 2022)
The purpose of this study is to identify the role of economic efficiency in achieving water sustainability in the West Bank and the Gaza Strip in Palestine. It adopts the qualitative analytical approach, through the analysis of reports, records and related data and placing them in the context of the research objectives and questions. The most important findings of the study were reaching three categories of challenges facing the role of economic efficiency associated with achieving water sustainability. Those challenges include the political aspect, including the domination of the Israeli occupation over the Palestinian resources and borders, and the violation of all water human rights; the geographical aspect and its connection to climate change, increased evaporation rates, over-extraction, and increased salinization of water basins; The administrative aspect, including the challenges of optimizing the use of available resources, and raising the allocative and technical efficiency of these resources. The study provided the policy makers with a set of recommendations mainly: to focus on generating mechanisms of international pressure to ensure mitigating the repercussions of the effects of the Israeli hegemony and prosecuting the Israeli occupation in international courts; to develop policies and measures that mitigate the effects of the climate change, high levels of evaporation and over-extraction of groundwater sources, increased salinization of water and soil; and the need to adopt a pioneering and advanced management approach by water service providers, in cooperation with policy and decision-makers in the Palestinian water and sanitation sector, in order to raise the degree of resilience and the rate of flexibility for water sustainability in Palestine.